Measuring attitude towards personal data for adaptive cybersecurity - Addae, Joyce Hoese; Brown, Michael; Sun, Xu; Towey, Dave; Radenkovic, Milena (Emerald, 2017)
Purpose: This paper presents an initial development of a Personal Data Attitude (PDA) measurement instrument based on established psychometric principles. The aim of the research was to develop a reliable measurement scale for quantifying and comparing attitudes towards personal data that can be incorporated into cybersecurity behavioral research models. Such a scale has become necessary for understanding individuals’ attitudes towards specific sets of data as more technologies are being designed to harvest, collate, share and analyze personal data.